Cross-Cultural Code-Switching: The Psychological Challenges of Adapting Behavior in Foreign Cultural Interactions - Molinsky, Andrew (Academy of Management Review, 2007)
Previous research on cultural adaptation has focused on the challenges and outcomes associated with long-term adaptation to a foreign culture. Little has focused on the dynamics of cultural adaptation within single interactions, which are the building blocks of these long-term patterns. I fill this gap by introducing the concept of cross-cultural code-switching and providing an account of the psychological challenges people face in successfully adapting their behavior in foreign cultural interactions.